Moderate Weight Loss Decreases Oxidative Stress and Increases Antioxidant Status in Patients with Metabolic Syndrome. (18th December 2012) - Del Ben, Maria; Angelico, Francesco; Cangemi, Roberto; Loffredo, Lorenzo; Carnevale, Roberto; Augelletti, Teresa; Baratta, Francesco; Polimeni, Licia; Pignatelli, Pasquale; Violi, Francesco
Abstract : Background . Oxidative stress is enhanced in metabolic syndrome (MetS) and believed to contribute to accelerated atherosclerosis. Weight loss is associated with lowered oxidative stress. Methods . We performed a cross-sectional study in 92 consecutive patients with metabolic syndrome and 80 without. A dietary intervention with moderately low-calorie diet (600 calories/day negative energy balance) was carried out in 53 of metabolic syndrome patients. Oxidative stress, assessed by sNOX2-dp and urinary 8-iso-PGF2 α, and antioxidant status, assessed by serum levels of vitamin E and adiponectin, were measured before and after 6 months. Results . Serum vitamin E/cholesterol ratio was significantly lower in metabolic syndrome compared to controls (P < 0.001 ) and decreased by increasing the number of metabolic syndrome components (P < 0.001 ). After six months, 23 and 30 patients showed >5% (group A) or <5% (group B) weight loss, respectively. Urinary 8-iso-PGF2 α (−39.0%), serum sNOX2-dp (−22.2%), adiponectin (+125%), and vitamin E/cholesterol ratio (+129.8%) significantly changed only in A group. Changes in body weight and in serum adiponectin were independent predictors of vitamin E/cholesterol ratio variation. Conclusion . Our findings show that in metabolic syndrome moderate weight loss is associated with multiple health benefits including not only oxidative stress reduction but also enhancement of antioxidant status.